A novel horA genetic mediated RCA detection of beer spoilage lactobacillus. (January 2018) - Yin, Hua; Dong, Jianjun; Yu, Junhong; Li, Yanmei; Deng, Yang
Abstract: As one of the most popular beverage, beer has strong resistance to bacteria except for lactic acid bacteria (LAB), as its strong viability in beer. Contaminating LAB results in beer spoilage. HorA gene carried by beer spoilage lactobacillus confers hop resistance and is associated with the growth of Lactobacillus in beer, thus can be used as a perfectly valid genetic marker for the detection of beer spoilage Lactobacillus strains. This study applied genome and bioinformatics analyses, together with genetic alignment and comparison techniques to build a rolling circle amplification (RCA) detection method targeted on horA for beer spoilage Lactobacillus. The horA genetic mediated RCA method showed rapid, sensitive and specific on beer spoilage lactobacillus detection. Highlights: HorA is a perfectly valid genetic marker suitable for detection of beer spoilage Lactobacillus strains. A RCA detection assay targeted on horA gene was developed and evaluated. The RAC detection assay is rapid, sensitive and specific on detection of beer spoilage Lactobacillus strains.